2019
DOI: 10.3390/children6020028
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Coping with Time-Related and Productivity Challenges of Young People with Learning Disabilities and Attention-Deficit/Hyperactivity Disorder

Abstract: Learning disabilities (LD) and attention deficit hyperactivity disorder (ADHD) are characterized by neurological differences that result in difficulties meeting learning and productivity expectations. Young people with LD and ADHD experience difficulties in self-managing academic, social, daily living, and health/wellness demands. Students with LD/ADHD must work longer and harder than peers, which makes managing time and productivity a critical skill for school success. This study examined the strategies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…As the data was not gathered to specifically explore the coping strategies used by young patients with brain tumours, and their parents, these findings provide only initial understandings of these [35]. It is possible (and quite likely) that CYP and parents engaged in more coping strategies, though did not discuss these as it was neither the focus of the research nor the interview questions.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…As the data was not gathered to specifically explore the coping strategies used by young patients with brain tumours, and their parents, these findings provide only initial understandings of these [35]. It is possible (and quite likely) that CYP and parents engaged in more coping strategies, though did not discuss these as it was neither the focus of the research nor the interview questions.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…Given the symptoms and academic challenges that students with ADHD often face (Budd et al, 2016;Kreider et al, 2019;Mayo Clinic, 2019) it is not surprising that the most frequently noted apps related to schoolwork. However, as mentioned earlier (Ahrens et al, 2019;CHADD, 2018), students with ADHD also have daily life demands that must be addressed in order to succeed in school.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data show that students with ADHD have difficulty with personal situations (e.g., study habits, motivation), and course-related self-efficacy (e.g., time management, keeping up-to-date with schoolwork) (Budd, Fichten, Jorgensen, Havel, & Flanagan, 2016). The following school related ADHD symptoms and challenges were recently reported by 52 college students: "staying focused, managing time, extensive writing assignments, reading comprehension of textbooks or academic publications, organization, completing homework, memorizing and retrieving information from memory, following multistep directions, expressing thoughts or opinions clearly, following others when they speak in conversation, applying different approaches to one problem, and initiating activities, tasks or independent ideas" (Kreider, Medina, & Slamka, 2019, Table 2). Considering these difficulties, it is not surprising that the academic performance of post-secondary students with ADHD is often poor (Budd et al, 2016).…”
Section: Importance Of the Problemmentioning
confidence: 99%
“…In addition, many SWDs face transportation issues, have trouble accessing technological advances (Spencer, 2017), have limited access to advanced coursework in mathematics and science (National Science Board, 2014), and face economic barriers that affect educational opportunities for future employment (Lapan et al, 2007). In addition, Kreider and colleagues (2019) reported that SWDs with “persisting cognitive deficits . .…”
Section: Experiences Of Swds In Afterschool Stemmentioning
confidence: 99%